Breakdown Voltage Characteristic Of Mineral Oil In Power Transformer 16 Mva Updl Semarang - Setyo Adi Nugroho; Setyo Aji Priambodo (Techno (Jurnal Fakultas Teknik, Universitas Muhammadiyah Purwokerto), 2020)
The transformer is one of the most important equipment in the electric power system, which is to distribute power from power plants to the load centers by step-up or step down the voltage. Transformer is expect to have a high level of reliability. One of the causes of damage to the power transformer is its insulation system. Mineral oil is an insulator that is widely used in power transformers. One of the important parameters in oil type insulation is the breakdown voltage value, the greater breakdown voltage value, as better the insulation quality. In this research, a breakdown voltage test is carried out on a Shell Diala B transformer oil type regarding the IEC 60156-95 standard. The results showed a breakdown voltage in the power transformer oil at UPDL Semarang of 49.2 kV. These results have met the feasibility standard of transformer oil, based on the IEC standard the value of breakdown voltage of liquid type insulation is 30 kV.